Bokashi Fertilizer Production from Waste Processing at Rusunawa Muara Baru - Renna Eliana Warjoto; Meda Canti; Anastasia Tatik Hartanti; Benedicta Evienia Prabawanti (Institute for Research and Community Services, 2020)
Waste that is not managed well may potentially cause diseases and negatively affect the quality of life. Rusunawa Muara Baru, Jakarta, is one of our partner communities that need continuous training in all aspects, including waste management. Therefore, the present community service program was carried out to educate the residents of Rusunawa Muara Baru on the importance of sorting waste and how to process household organic waste into liquid organic fertilizer and bokashi compost. The program was conducted twice in two weeks. At the first meeting, an introductory questionnaire was distributed, an interactive discussion was performed, and a fertilizer production workshop using simple composters was initiated. Two weeks later, the composting results were evaluated, and the participants filled out the evaluation questionnaire. Approximately 83% of the participants agreed to sort household waste after the program was completed, which showed the participants' increasing awareness in waste processing. The liquid biofertilizer produced was used for planting vegetable seeds even though it still had a foul odour. The quality of the compost produced, however, was still below expectations. We suggest that in the future, education and workshops on simple household-scale composting methods capable of producing good quality liquid organic fertilizer and compost without odour should be conducted.